PHYTOCHEMICAL INVESTIGATION AND ANTI-CANCER ACTIVITY OF AERIAL PARTS OF VINCA DIFFORMIS (AYUSHDHARA, 2016)
The study aimed to investigate the phytochemical and therapeutic effects of aerial parts of Vinca difformis for anticancer activity in normal and cyclophosphamide induced oxidative stress in mice brain. Aerial parts of Vinca difformis was extracted with ethanol:acetone mixture. Following extraction,extract was tested for the presences of phytochemical constituents and cyclophosphamide induced oxidative stress in mice brain. Presences of alkaloid, glycosides, steroids, phenolic compounds and volatile oils were identified in the extract. Among these total alkaloid content was 8% and 0.348mg/mg gallic acid was obtained from the extract. Vinca difformis extract was effective as antioxidant to reduce the cyclophosphamide toxicity. Thus the results suggests that the aerial parts of Vinca difformis extract contains some active principles which may possess significant anti-cancer activity.